Risks and burden of lung cancer incidence for residential petrochemical industrial complexes: A meta-analysis and application. (December 2018) - Lin, Cheng-Kuan; Hsu, Yu-Tien; Christiani, David C.; Hung, Huei-Yang; Lin, Ro-Ting
Abstract: Background: Lung cancer is one of the most common cancers in the world. Higher incidence of lung cancer may be associated with residential proximity to a petrochemical industrial complex (PIC) due to exposure to various carcinogens, although results from previous epidemiologic studies remain inconclusive. Because disease burden due to residential inequality is a public health and societal concern, this study analyzed published data to estimate lung cancer incidence in association with residential proximity to PICs. Methods: We performed a meta-analysis on selected epidemiologic studies that met the following criteria: lung cancer incidence was coded by the International Classification of Diseases; exposure groups were clearly defined as residents living near PICs; and confidence intervals were available or calculable from original articles. We further applied a population attributable factor (PAF) method to estimate disease burden attributable to living near PICs in 22 European Union (EU) countries. Results: Meta-analysis included six studies with a total of 466, 066 residents living near PICs in six countries. Residents living near PICs had a 19% higher risk of lung cancer compared to those who lived farther away (95% CI = 1.06–1.32). By sex, risks were higher and more significant for females (RR = 1.29; 95% CI = 1.09–1.54; P = 0.004) than males (RR = 1.12; 95% CI = 0.95–1.33; P = 0.173). By location, only groups in Europe had a significantly greater risk of lung cancer with exposure to PICs (95% CI = 1.03–1.33; P = 0.019), although groups in other locations showed similar trends. By bona fide observation, observation of residents for at least seven years provided sufficient latency to estimate risk (RR = 1.25; 95% CI = 1.17–1.34; P < 0.001). Regarding burden of lung cancer in 22 EU countries, 494 males and 478 females were attributed to living in the vicinity of a PIC annually. Conclusions: Lung cancer incidence is significantly higher in individuals living near PICs. This result provides strong epidemiologic evidence for further policy to regulate potential pollutants near PICs. Highlights: Higher incident rates of lung cancer for residents living close to petrochemical industry complex Highlights: Petrochemical industry complex usually involves toxic chemicals in manufacturing processes. Residents nearby petrochemical industrial complex might be exposed to various carcinogens. Higher incident rates of lung cancer for residents living nearby petrochemical industry complex Higher risks in females, Europe, and studies with longer observation period and specific chemical exposure Establish local policy to regulate potential pollutants near petrochemical industry complex